Clinical Outcome of Patients with Diffuse Axonal Injury Receiving Adrenocorticotropin Analogue at Dr. Soetomo Hospital - Wahyuhadi, Joni; Wicaksono, Pandu; Notobroto, Hari Basuki (Folia Medica Indonesiana, 2018)
Brain traumatic injury (BTI) is one of the causes of death and disability worldwide that affects people regardless of sex, age, income and social status, race, or nationality. In patients with brain traumatic injury, one of the problems that occurs is Diffuse Axonal Injury (DAI) that can produce a direct clinical effect, leading to coma and death. Adrenocorticotropin analogues (ACTH) is one of neuroprotective therapy in brain injury. The aim of this study was to analyze the effect of ACTH analogue on the clinical output (Glasgow Outcome Score/GOS and Bartle Index) in patients with DAI at hospital discharge, 3 months and 6 months post-treatment. This study revealed that ACTH analogue administration resulted in higher GOS and Barthel Index scores than that in control. Further study will required with other variables, such as cognitive and motor examination, and some biomarkers can also be examined serially.